آثار استخدام اللغـــــــة الام عند تدريس اللغة الانجليزيــــــــة - الفرجاني الخادمة الطاهر (مجلة الاصالة, 2026)
There has long been debate concerning using L1 in L2 lessons. According to Krashen (1981), extensive exposure to L2 is necessary for L2 learning to be successful. Furthermore, he claims that having access to L1 is what leads to failure in L2 exposure. In contrast to Krashen’s theory, several academics stated that using L1 in L2 classrooms proves to be beneficial to learners. This research aimed to find out the effect of using first language (L1) when teaching English language. The data were obtained from questionnaires distributed to 60 teachers. The other research sample consists of 8 male and female teachers from 6 secondary public schools in Libya. The different schools in this study were chosen randomly using stratified random sampling. Those 8 teachers were interviewed to discover their preceptions towards the effects of applying L1 in L2 classes. The study addressed various issues that may influence teachers’ practices, including teachers’ perceptions towards the processes of using L1 inside English classes. The results of the questionnaire revealed that 75% of the teachers stated that L1 should be used when explaining difficult concepts . In addition, the results of the interviews revealed that six out of eight teachers were quite sure that using L1 helps students to feel more secure and confidents to